2005
DOI: 10.1002/ana.20410
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes of the N88S Berardinelli–Seip congenital lipodystrophy 2 mutation

Abstract: Recently, two missense mutations (N88S, S90L) in the Berardinelli-Seip congenital lipodystrophy gene have been identified in autosomal dominant distal hereditary motor neuropathy and Silver syndrome. We report the phenotypic consequences of the N88S mutation in 90 patients of 1 large Austrian family and two unrelated German families. Variation in the clinical and electrophysiological phenotype enabled us to distinguish six subtypes. In 4.4%, the disorder was not penetrant. Twenty percent of the patients were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
84
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 22 publications
9
84
0
Order By: Relevance
“…In a number of families diagnosed as either dHMN-V or SS two heterozygous mutations (N88S, S90L) located in exon 3 in the Berardinelli-Seip congenital lipodystrophy gene (BSCL2) were identified [11]. Clinical examination of more than 90 patients with the BSCL2 N88S substitution showed that it is most often associated with a dHMN-V phenotype and less frequently, additional prominent spasticity and mild sensory disturbances are found in the lower limbs [2,[12][13][14][15]. Up to date, the S90L substitution was only described in three families and often resulted in a spastic paraplegia phenotype with marked weakness and wasting in the hands suggesting the clinical diagnosis of SS [11,15,16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a number of families diagnosed as either dHMN-V or SS two heterozygous mutations (N88S, S90L) located in exon 3 in the Berardinelli-Seip congenital lipodystrophy gene (BSCL2) were identified [11]. Clinical examination of more than 90 patients with the BSCL2 N88S substitution showed that it is most often associated with a dHMN-V phenotype and less frequently, additional prominent spasticity and mild sensory disturbances are found in the lower limbs [2,[12][13][14][15]. Up to date, the S90L substitution was only described in three families and often resulted in a spastic paraplegia phenotype with marked weakness and wasting in the hands suggesting the clinical diagnosis of SS [11,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Silver syndrome (SS) is a rare motor neuron disease which also frequently resembles a dHMN-V phenotype as patients often show prominent amyotrophy of the small hand muscles [5]. The presence of mild to severe pyramidal tract signs is common in dHMN-V and SS whereas they have rarely been observed in patients with CMT2D [1,2,5,6]. Initially, the presence of spastic paraparesis has led to the subclassification of SS among the group of hereditary spastic paraplegias (HSP) and SS was thus termed as SPG17 [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In families with the seipin/BSCL2 mutation, the frequency of an HSP phenotype has been observed to be as high as 10% of patients [1]. The other 46 patients in our study had symptomatic UMN involvement of the arms or bulbar region, which may suggest a diagnosis of PLS [6,10].…”
Section: Sirsmentioning
confidence: 49%
“…The role of other HSP genes in sporadic upper motor neuron (UMN) syndromes is largely unknown. Two known mutations (c.263G[A/p.N88S and c.269C[T/p.S90L) in exon 3 of the seipin/BSCL2 gene (SPG17) can cause a range of AD (mixed) upper and lower motor neuron disorders, including Silver syndrome (HSP with amyotrophy of the hands), variants of Charcot-Marietooth disease type 2, distal hereditary motor neuropathy type V (dHMNV), but also pure and complicated forms of HSP [1,13,14]. Because of incomplete penetrance, the seipin/ BSCL2 mutation can manifest as a sporadic disease [14].…”
Section: Sirsmentioning
confidence: 99%